Development of Simulation Scenario for the Circulatory System in Humans Material for Grade XI High School - Saputri, Winda Eka; Hamka L, Hamka L; Rachmawaty, Rachmawaty (Biology Teaching and Learning, 2023)
This research aims to produce simulation scenarios for biology materials in Grade XI of Senior High School focusing on the mechanism of human blood circulation. The type of research used is R&D research employing the 4D development model (Define, Design, Develop, and Disseminate). The validity and simulation scenarios were assessed by two validated biologist experts from the Faculty of Mathematics and Natural Sciences (FMIPA) at UNM, using simulators and simulation scenario questionnaires. Based on the questionnaire data obtained, the validity of the simulation scenario is Va = 4.12, which falls into the "valid" category (3.5 ≤ Va ≤ 4.5). The practicality of the simulation scenarios was assessed by collecting data through teacher and student assessments based on a practicality assessment questionnaire. The obtained data showed an average percentage of all aspects at 87.41%, indicating a very positive teacher response to the circulation mechanism simulation scenario, while data based on student responses showed an average percentage of all aspects at 82.62%, indicating a positive response from students to the circulatory mechanism simulation scenario. Based on the research conducted, it can be concluded that the simulation scenario for the human circulation mechanism is both valid and practical.Keywords: Simulation scenario, simulation method, 4D, validity, practicality